2012
DOI: 10.1017/jie.2012.24
|View full text |Cite
|
Sign up to set email alerts
|

‘For the Life of Me, I Can't See Why Those Students were Let Go on So Long’: Educating the Educators, Aboriginal and Torres Strait Islander-Style

Abstract: In 2008, almost 40% of Aboriginal and Torres Strait Islander students enrolled in the Graduate Diploma in Indigenous Health Promotion at The University of Sydney failed to complete the course. Although this was not considered unusual when compared to previous years, the decision was made to investigate why so many students struggled to meet the expectations of a course that was pedagogically progressive, culturally affirming, taught by highly regarded academics and strongly supported by the university and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…[2] The importance of including this information in formal education was a key step to reconciliation as outlined by various Calls to Action. [6] Four studies [8,[13][14][15] in this literature review supported the TRC assertion that Indigenization of post-secondary institutions was essential. Predictably, having a culturally diverse curriculum in a culturally-diverse setting was important.…”
Section: Indigenization Of Post-secondary Institutionsmentioning
confidence: 52%
See 2 more Smart Citations
“…[2] The importance of including this information in formal education was a key step to reconciliation as outlined by various Calls to Action. [6] Four studies [8,[13][14][15] in this literature review supported the TRC assertion that Indigenization of post-secondary institutions was essential. Predictably, having a culturally diverse curriculum in a culturally-diverse setting was important.…”
Section: Indigenization Of Post-secondary Institutionsmentioning
confidence: 52%
“…[12] Indigenous nurse academics and Indigenous staff supports were beneficial as role models and for their role in promoting success. [8,15] The articles reviewed agreed on the importance of Indigenizing both the environment and curriculum, while ensuring Indigenous role models were present among staff members. [8,[13][14][15]…”
Section: Indigenization Of Post-secondary Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatedly, positive experiences in the classroom (Bandias et al 2014;Hossain et al 2008;Shah and Widin 2010) and experiences at university that increase selfesteem and confidence (Bandias et al 2014;Plater 2013) have been identified as The participation of Australian Indigenous students… 333 vital for some students. Access to appropriate information, infrastructure, and resources within the university has also been highlighted (Barney 2013;Hossain et al 2008;Oliver et al 2013Oliver et al , 2015Usher et al 2005), facilitated through support services and programs (Barney 2013;Fleet et al 2007;Hossain et al 2008;Morgan 2001;Oliver et al 2013;Shah and Widin 2010;Usher et al 2005).…”
Section: Enablers To Participation Retention and Completion In Highmentioning
confidence: 99%
“…Institutional barriers were a major focus of many articles, and included a perceived lack of support and obstacles in accessing the anticipated or required information; these challenges can culminate in students feeling unequipped to navigate the university system (Aseron et al 2013b;Asmar et al 2015;Cameron and Robinson 2014;DiGregorio et al 2000;Ellender et al 2008;Fleet et al 2007;Gibb 2006;Howlett et al 2008;Kinnane et al 2014;Kippen et al 2006;Oliver et al 2013Oliver et al , 2015Plater 2013;Rigby et al 2010;Trudgett 2009;Usher et al 2005). Closely connected is the inclusion/exclusion of Indigenous content; in some instances there was a lack of identifiable content in the curriculum; in others, the content was perceived as culturally inappropriate or incorrect (Aseron et al 2013b;Cameron and Robinson 2014;Gibb 2006;Oliver et al 2013;Rigby et al 2010;Sonn et al 2000;Usher et al 2005).…”
Section: Barriers To Participation Retention and Completion In Highmentioning
confidence: 99%